Mendongeng: - Uniawati Uniawati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
Lack of children’s appreciation to literary works is caused by the lack of literary knowledge.Children are rarely introduced to literary works which stretch the distance between children and literature. This paper is a form of thinking of how to foster a sense of concern for the children to literature through fairy tales that children will love and be appreciative with literature and literary works. Parents as the party that hold the main contribution to the formation of a child’s personality are more active by providing the fairy tales that align the needs of children. Through stories, children can be taught to know better the literature,enjoy, and feel the benefits. Fairy tales are not just providing entertainment for children, but also providing a much more extensive education on children’s moral, ethical, and noble character without feeling patronized and lectured.